A FUNDAMENTAL ANALYSIS OF BREAST CANCER'S ESTROGEN RECEPTOR SIGNALING PATHWAYS - Abbas Sadiq Alqaisi, Ali; Haider Abbas Jasim, Hawraa; Haider Saleh, Areej; Ayad Kazem, Rafal; Abbas Fadhel, Afnan; Ali Kashkul, Saja (PT. Antis International Publisher, 2025)
Objective: This mini-review aims to provide a comprehensive overview of estrogen receptor (ER) signaling pathways in breast cancer, emphasizing their implications for therapeutic resistance and novel treatment strategies. Method: A critical analysis of recent literature was conducted, focusing on molecular mechanisms associated with ER signaling, including alterations in the ESR1 gene, PI3K pathway activation, and dysregulation of cell cycle control. Results: Findings reveal that approximately two-thirds of breast cancers are hormone-dependent and rely on estrogen and progesterone receptor signaling for growth. While antiestrogens remain the cornerstone of hormone therapy, resistance often emerges through diverse molecular pathways. The development of resistance has driven the advancement of targeted therapies such as selective estrogen receptor degraders (SERDs) and combination regimens involving CDK4/6 or PI3K inhibitors. Novelty: This review highlights the evolving understanding of ER signaling in breast cancer and underscores the necessity of targeting specific molecular alterations to overcome resistance. By integrating recent advances in molecular oncology, the study supports the development of more personalized and effective therapeutic strategies for hormone receptor-positive breast cancer.